Quality assessment of oral health promotion contents regarding caries, periodontal disease, and oral cancer through websites using discern instruments: a cross-sectional study - Halim, Muhammad Abdul; Suwargiani, Anne Agustina; Aripin, Dudi; Marhazlinda, Jamaludin (Universitas Padjadjaran, 2024)
ABSTRACTIntroduction: One way to improve public oral health is through conducting health promotion activities. As technology develops, the internet has been used as a medium for health promotion by presenting health content through websites. However, the use of these websites has the potential to provide inaccurate health information due to the flexibility of users in uploading health content without a prior regulatory process and review of the contents. This study aims to describe oral health promotion content quality through regarding caries, periodontal disease, and oral cancer websites using Discern Instruments. Methods: This study used the descriptive method with a cross-sectional approach. Samples were taken using the purposive sampling technique, with a total of 46 samples. The instrument consisted of 16 questions divided into three sections. The first section, comprising seven questions, focused on the reliability and accuracy of the presented health information. The second section, with eight questions, focused on the quality of information regarding treatment options. The final section, consisting of a single question, assessed the overall assessment based on the previous questions. The quality of the websites was assessed by two reviewers. The inter-rater reliability between the two reviewers was calculated using the Cohen’s Kappa test. Data presentation included frequency distribution, mean, and standard deviation. Results: In this study, 33.3% of caries websites had low quality and 66.6% had moderate quality. In periodontal disease, 33.3% of websites were of low quality, 60% were of moderate quality and 6.6% were of high quality. In oral cancer, 26.3% were of low quality and 73.6% were of medium quality. Conclusion: The quality of dental and oral health promotion content on websites, assessed using the Discern Instruments, shows that most websites regarding caries, periodontal disease, and oral cancer have moderate quality, some have low quality, and only one website is of high quality.